2012
DOI: 10.5430/elr.v1n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Structure Dependent Narrative Features in Modeled Contexts: African American and European American Children

Abstract: The purpose of this study was to describe similarities and differences in structure-dependent features of narratives produced by 132 typically developing African American (AA) and European American (EA) children in a modeled elicitation context, across three age groups. Participants included 132 AA and EA children matched for gender, age, and geographic region. Children were divided into young, middle, and older elementary age groups. After listening to a model narrative and answering questions about it, child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 54 publications
0
9
1
Order By: Relevance
“…Helping diverse preschool children with and without language impairment improve their narrative language could have an even greater impact on their ability to navigate an ethnocentric, mainstream school curriculum. Such interventions should not be considered a replacement for each child's micro-or macrocultural approach to narration, which can be considerably different from what is reinforced in U.S. schools (Champion, 1998;Currenton & Justice, 2004;Gillam, Fargo, Petersen, & Clark, 2012;Gorman, Fiestas, Peña, & Clark, 2011;Heath, 1983;Mills, Watkins, & Washington, 2013;Westby, 1994). Instead, narrative language intervention should be considered a way to expose children to the mainstream narrative language dialect expected of them in the school culture, allowing them to be multidialectal and multicultural.…”
Section: Story Grammarmentioning
confidence: 99%
“…Helping diverse preschool children with and without language impairment improve their narrative language could have an even greater impact on their ability to navigate an ethnocentric, mainstream school curriculum. Such interventions should not be considered a replacement for each child's micro-or macrocultural approach to narration, which can be considerably different from what is reinforced in U.S. schools (Champion, 1998;Currenton & Justice, 2004;Gillam, Fargo, Petersen, & Clark, 2012;Gorman, Fiestas, Peña, & Clark, 2011;Heath, 1983;Mills, Watkins, & Washington, 2013;Westby, 1994). Instead, narrative language intervention should be considered a way to expose children to the mainstream narrative language dialect expected of them in the school culture, allowing them to be multidialectal and multicultural.…”
Section: Story Grammarmentioning
confidence: 99%
“…because, then, when, where) conjunctions, along with the literate language features, create the microstructural elements of narratives (Gillam et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…() found that among a sample of African American 11‐ and 12‐year‐olds, girls produced more complex narratives than did boys. Other more recent studies find no difference in the narrative production by gender among African American children (e.g., Gillam et al., ; Hester, ). The inconsistencies in these studies may reflect the differences in the ages assessed and methodologies used, but leave unanswered questions about how narratives may differ by gender among preschool African American children and the implications of any potential differences for later reading outcomes.…”
Section: Conceptual Frameworkmentioning
confidence: 84%
“…One way of addressing this issue is to elicit children's narratives using a structured task that focuses on a protagonist involved in a series of goal‐directed behaviors to resolve a problem as the story grammar approach is most closely aligned with this type of task. Previous studies support the use of the story grammar approach as an effective way of assessing the oral narratives of young African American children (e.g., Brown et al., ; Gillam et al., ; Price et al., ).…”
Section: Conceptual Frameworkmentioning
confidence: 87%